Extraction of endo-pectinase activity from the culture filtrate of Polyporus squamosus by aqueous two-phase systems composed of low molecular mass polyethylene glycol and phosphate salt - Peričin Draginja M.; Radulović Ljiljana M.; Ćurčin Senka S. (Acta Periodica Technologica, 2004)
Separation of endo-pectinase activity from the culture filtrate of Polyporus squamosus - strain MMOL76, by aqueous two-phase partitioning technique in polyethylene glycol/sodium dihydrogen phosphate system was investigated as the first operation in the downstream processing of enzyme. The best results concerning the partitioning coefficient and the top phase yield were achieved in the polyethylene glycol 400/sodium dihydrogen phosphate system at the tie-line length 78.9 % at pH 3.8 (K = 8), with a 90% yield.